How context shapes neural decision processing across the lifespan: evidence from an event-related potential study. - Fernandes, Carina; Macedo, Inês; Mata, Rui; Danese, Giuseppe; Barbosa, Fernando; Marques-Teixeira, João (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2026)
Objectives Understanding how aging shapes neural mechanisms of decision-making across diverse contexts is critical to promote adaptive choices throughout the lifespan. To this purpose, we examined how age and decision context influence neural processes preceding and following decisions. Methods Seventy-five healthy adults (20–80 years) performed three versions of the Monetary Incentive Delay task while EEG was recorded: a standard risk-based task, a social variant (outcomes benefiting another person), and an uncertainty variant (cue–outcome contingencies learned through feedback). We analyzed event-related potentials (ERPs) indexing anticipatory processing (Cue-P3), motor preparation (CNV), motivated action (Target-P3), earlier feedback appraisal (FRN), and later evaluative outcome processing (Feedback-P3). Results Older adults exhibited attenuated Cue-P3 and Target-P3 amplitudes relative to younger adults across decision contexts. In the remaining ERP components, the overall ERP amplitudes were preserved, but the differentiation between incentivized and neutral conditions was reduced in older adults. Decision context modulated neural responses across all groups: social and uncertainty contexts elicited enhanced Cue-P3, Target-P3, and Feedback-P3 amplitudes compared to the risk context, indicating greater attention and motivational engagement. Notably, context effects were consistent across age groups, with no significant interactions between age and context, highlighting preserved sensitivity to social and learning demands in older adults. Discussion These findings suggest that while aging selectively reduces affective processing of incentives, neural responsiveness to contextual factors may remain robust across adulthood, underscoring the potential of socially meaningful and learning-rich environments to sustain decision engagement in later life.